2013
DOI: 10.1371/journal.ppat.1003342
|View full text |Cite
|
Sign up to set email alerts
|

Broadly Neutralizing Antibody PGT121 Allosterically Modulates CD4 Binding via Recognition of the HIV-1 gp120 V3 Base and Multiple Surrounding Glycans

Abstract: New broad and potent neutralizing HIV-1 antibodies have recently been described that are largely dependent on the gp120 N332 glycan for Env recognition. Members of the PGT121 family of antibodies, isolated from an African donor, neutralize ∼70% of circulating isolates with a median IC50 less than 0.05 µg ml−1. Here, we show that three family members, PGT121, PGT122 and PGT123, have very similar crystal structures. A long 24-residue HCDR3 divides the antibody binding site into two functional surfaces, consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
320
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 276 publications
(339 citation statements)
references
References 75 publications
16
320
2
1
Order By: Relevance
“…The cleaved SOSIP.R6 trimers were regular and homogeneous ( Fig. 4 A and B), consistent with earlier reports of the same construct (there designated BG505 SOSIP.664 gp140) (17)(18)(19). A semiquantitative analysis of the class averages showed that ∼100% of the SOSIP.R6 trimer images resembled virion-associated, native trimers from HIV-1 BaL (EMDB-5019) (Fig.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…The cleaved SOSIP.R6 trimers were regular and homogeneous ( Fig. 4 A and B), consistent with earlier reports of the same construct (there designated BG505 SOSIP.664 gp140) (17)(18)(19). A semiquantitative analysis of the class averages showed that ∼100% of the SOSIP.R6 trimer images resembled virion-associated, native trimers from HIV-1 BaL (EMDB-5019) (Fig.…”
Section: Resultssupporting
confidence: 89%
“…Thus, cleaved, SOSIP-stabilized BG505 gp140 trimers [SOSIP.R6; referred to elsewhere as "SOSIP.664" (17-19)] are highly homogeneous and their configurations resemble native Env spikes, as judged by negative-stain EM (17)(18)(19) (Fig. 4 A and B).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on an analysis of 50 bnAbs, we first defined mutational patterns that are statistically associated with resistance and sensitivity, using phylogenetically corrected methods (17), for four classes of bnAbs: the CD4 binding site; a trimer-specific, glycan-dependent V1V2 region; an N332-glycan-dependent V3 region; and the membrane proximal external region (MPER). The CH120.6 sequence retained key epitope-defining patterns of specific amino acid residues and N-linked glycosylation sites in these bnAb epitopes (18)(19)(20). We then used these signature patterns to predict the relative sensitivity of CH120.6 to the different antibodies shown in Table S2 using the machine-learning strategy Random Forests (21) implemented in the Python package scikitlearn (22).…”
Section: Resultsmentioning
confidence: 99%